Critical Steps At Preparation and Evaluation Procedures in Ivf Laboratories - Özgüner, Meltem; Dabak, D. Özlem (Fırat University, 2003)
First successful medical achievement in In Vitro Fertilization (IVF) techniques was the announcement of Louise Brown in July 1978 in United Kingdom. Embryologists have a duty to apply correct and justified IVF procedures that will conclude good practice in the laboratory. The main steps of IVF laboratory procedures, these are aimed to give support and guidance to the laboratory staff are summarized. These steps will assist staff in achieving the best outcome for IVF patients. Successful results mainly depends on clinician and embryologist's participation and cooperation in IVF-ET (In Vitro Fertilization-Embryo Transfer) cliniques. For a complete evaluation of the results, this analysis should be performed in cooperation with the clinical staff.

İn vitro fertilizasyon (IVF) tekniklerinin tıp alanındaki uygulanımının ilk başarısı 1978 yılının Temmuz ayında İngiltere'de Louise Brown adı verilen bebeğin doğumudur. Embriyologlar, laboratuvarda başarılı sonuçlar alınabilmesi için gerekli ve doğru işlemlerin uygulanmasından sorumludurlar. Laboratuvar çalışanlarına yardımcı olmak ve yol göstermek amacıyla IVF işlemlerinde önemli basamaklar özetlenmiştir. Bu basamaklar en iyi IVF sonuçlarının alınmasına yardımcı olacaktır. IVF-ET (İn Vitro Fertilizasyon-Embriyon Transferi) kliniklerinde başarılı sonuçlar alınabilmesi öncelikle klinisyen ve embriyoloğun işbirliği ve uyumuna bağlıdır. Sonuçların tam bir değerlendirmesi için bu analizlerin klinik çalışanları ile işbirliği içinde yapılması şarttır.
İn Vitro Fertilizasyon Laboratuvarında Hazırlık ve Değerlendirme Aşamalarında Önemli Basamaklar